Digitization Technologies and Contributions to Companies towards Accounting and Auditing Practices - Fahmi, Muhammad; Muda, Iskandar; Kesuma, Sambas Ade (Ridwan Institute, 2023)
The purpose of this study is to examine the development of digital technology, including blockchain technology, cloud computing and big data contributing to companies, as well as accounting and auditing practices. The study method uses a systematic literature review (SLR) with a bibliometric approach. The results of the study show that the consistent use of blockchain technology, cloud computing and big data has contributed to increasing organizational effectiveness and efficiency, but the problem of high costs, as well as data security and confidentiality are the most important issues in using these three digital technologies.